1982
DOI: 10.1073/pnas.79.17.5287
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen-transformed human cells are inhibited from entry into S phase by fusion to senescent cells but cells transformed by DNA tumor viruses overcome the inhibition.

Abstract: With parameters of transformation other than immortality (3). Another logical possibility is that the ability to induce DNA synthesis in senescent HDC might be associated with viral transformation. Cells transformed by viruses may have gained a factor that overrides the inhibitory effect of senescent HDC, whereas carcinogen-transformed cells may have lost a normal factor necessary for the expression ofsenescence while retaining their sensitivity to the putative inhibitor when it is supplied to them in heterodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…5), it is possible that the altered events in senescent HDF are clustered in just one or a few pathways that are deficient in senescent HDF. Prereplicative events that are altered in serum-stimulated senescent HDF include failure to show increased levels of c-fos (15) and cdc2, failure to phosphorylate RB protein (16), failure to abolish the inhibitor of entry into S phase as measured by the heterokaryon assay (22,36), and failure to enter S phase (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5), it is possible that the altered events in senescent HDF are clustered in just one or a few pathways that are deficient in senescent HDF. Prereplicative events that are altered in serum-stimulated senescent HDF include failure to show increased levels of c-fos (15) and cdc2, failure to phosphorylate RB protein (16), failure to abolish the inhibitor of entry into S phase as measured by the heterokaryon assay (22,36), and failure to enter S phase (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…(i) Unphosphorylated RB protein, a putative inhibitor of cell proliferation (39), is likely to be at least one component ofthe inhibitor of entry into S phase measured by the heterokaryon assay because only cells that contain RB-binding oncoproteins-i.e., SV40 T-antigen, adenovirus ElA, and HPV E7-are able to overcome the inhibitory effect of senescent HDF in heterokaryons (22 serum-stimulated, they go through a number of prereplicative steps before they enter S phase. All of the events illustrated are changes in gene expression except "PO4-RB," which means phosphorylation of RB protein, and "Abolish DNA Synthesis Inhibitor," which refers to loss of the ability to inhibit entry into S phase in replicating HDF in the heterokaryon assay (22,36). A majority of these prereplicative events still occurs in serum-stimulated senescent HDF even though these cells are unable to enter S phase (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…INK4A in inducing senescence in human head and neck keratinocytes revealed a correlation between the loss of p16 INK4A expression and keratinocyte immortality in several keratinocyte cell lines (Loughran et al, 1996) showed that the cell cycle block in senescent cells is not completely irreversible; when senescent ®broblasts were fused to SV40 transformed cells, DNA synthesis was induced in the senescent nuclei in the heterodikaryons (Stein et al, 1982), most likely as an eect of SV40 large T antigen. In senescent human diploid ®broblasts the p16…”
Section: Ink4amentioning
confidence: 99%
“…(Stein et al, 1982). However, when senescent eclls were fuscd with immortal ccII lines containing DNA tumor virus, the immortal lines were able to overcome the inhibition of DNA synthesis.…”
mentioning
confidence: 99%